The Dead Sea scrolls : forty years of research - Dimant, Devorah.; Rappaport, Uriel, 1935- (Studies on the Texts of the Desert of Judah, 1992)
A fortieth anniversary is an occasion to be marked under any circumstances, especially when it concerns a discovery as significant as that of the Dead Sea Scrolls. The proper way to mark this occasion was to organize a symposium that would be as comprehensive as possible, both in content and in variety of approaches, and which would be held in the land of the Scrolls. The papers here reflect not only the variety and richness of subjects treated by contemporary research on Qumran, but also its international character. Since the study of texts remains the first task of the Qumran scholar many of the collection's papers belong to its first section - Texts and Text Studies . The other six sections are: The History of the Qumran Community, Halakha at Qumran, Qumran and the Hebrew Bible, Qumran and the New Testament and The Hebrew of the Dead Sea Scrolls .